2014
DOI: 10.1371/journal.pone.0087186
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Social Environment Imprints Female Preference for Male Song in Mice

Abstract: BackgroundSexual imprinting is important for kin recognition and for promoting outbreeding, and has been a driving force for evolution; however, little is known about sexual imprinting by auditory cues in mammals. Male mice emit song-like ultrasonic vocalizations that possess strain-specific characteristics.ObjectivesIn this study, we asked whether female mice imprint and prefer specific characteristics in male songs.Methods and FindingsWe used the two-choice test to determine the song preference of female C57… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
103
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(122 citation statements)
references
References 24 publications
7
103
4
Order By: Relevance
“…A previous study has revealed that females in pro-estrus or estrus do not show the preference for USVs of males of a different strain observed here 14 . Therefore, only females in diestrus were used in the present study; in general, when using females for this test, the phase of the estrous cycle should be known.…”
Section: Discussioncontrasting
confidence: 47%
See 3 more Smart Citations
“…A previous study has revealed that females in pro-estrus or estrus do not show the preference for USVs of males of a different strain observed here 14 . Therefore, only females in diestrus were used in the present study; in general, when using females for this test, the phase of the estrous cycle should be known.…”
Section: Discussioncontrasting
confidence: 47%
“…In a previous study, the preference of females for some USVs over others was potentiated when they were exposed to male-soiled bedding, or to the male pheromone ESP1 25 before behavioral testing. In the absence of male-odor stimuli, females did not show a preference for USVs of males of a different strain 14 .…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Female urine, but not male urine, also provokes male mice to emit USVs (30). The USVs of male mice attract females and contribute to mate choice by females (31,32). We then examined if this female urine-induced social behavior is altered in ΔD mice.…”
Section: Resultsmentioning
confidence: 99%